Non-Destructive Assessment of Concrete Structures: Reliability and Limits of Single and Combined Techniques State-of-the-Art Report of the RILEM Technical Committee 207-INR - Breysse, Denys; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2012)
This book gives information on non destructive techniques for assessment of concrete structures. It synthesizes the best of international knowledge about what techniques can be used for assessing material properties (strength) and structural properties (geometry, defects...). It describes how the techniques can be used so as to answer a series of usual questions, highlighting their capabilities and limits, and providing advices for a better use of techniques. It also focuses on possible combinations of techniques so as to improve the assessment. It is based on many illustrative examples and give in each case references to standards and guidelines.
List of contributors -- Foreword -- 1. Non destructive assessment of concrete structures: usual combinations of techniques -- 2. Presentation of common non destructive techniques -- 2.1 Ultrasonic through transmission -- 2.2. Ultrasonic-echo;2.3. Surface Waves methods -- 2.4. Impact-Echo -- 2.5. Impulse response -- 2.6. Acoustic Emission -- 2.7. Ground penetrating radar -- 2.8. Capacitive technique -- 2.9. Electrical resistivity measurement -- 2.10. Infrared thermography -- 2.11. Radiography -- 2.12. Rebound hammer -- 2.13. Pull-out testing -- 3. Estimation of on-site compressive strength of concrete -- 4. Control of thickness/dimensions of pavements, foundations, elements and piles -- 5. Assessment of bonding, delamination and interfaces -- 6. Localization of grouting faults in post-tensioned concrete structures -- 7. Rupture of prestressing cables -- 8. Non destructive assessment of concrete structures: combination of techniques for addressing new challenges -- Keyword index.
Keywords: Engineering; Building construction; Materials; Engineering; Building Materials; Structural Materials; Building Repair and Maintenance